Osmoregulators in Hymenaea courbaril and Hymenaea stigonocarpa under water stress and rehydration - de Souza, Luma Castro [UNESP]; da Luz, Luana Moraes; da Silva Martins, Jéssica Taynara; de Oliveira Neto, Cândido Ferreira; Palheta, Juscelino Gonçalves; de Oliveira, Tamires Borges; Alves, Ediane Conceição; de Almeida, Risely Ferraz [UNESP]; de Oliveira, Raimundo Leonardo Lima; da Costa, Roberto Cezar Lobo; Vilhena, Nariane Quaresma (Springer Nature, 2018)
The objective of this work was to evaluate the effect of different water deficiency and rehydration levels on the concentrations of osmoregulators in two plant species (Hymenaea courbaril and H. Stigonocarpa) in the Amazon. We adopted a 2 × 5 × 5 factorial system, referring to 2 species (H. courbaril and H. stigonocarpa) and 5 stages of hydration and rehydration. The five hydration and rehydration stages were established in: (1) Control treatment E0; (2) Plants with 13 days of stress after incubation—E13; (3) Plants with 26 days of stress E26; (4) The plants that were established after 26 days after incubation and rehydrated for two days (RD2); (5) rehydrated for two days (RD4). The plants that were established after 26 days after incubation and rehydrated for four days. The experiment totaled fifty young plants with five replicates. Biochemical measurements were performed at the beginning of the experiment (E0) at 13 (E13) and 26 (E26) days after the water stress, in which the plants were rehydrated, repeating the analyses after two (RD2) and four (RD4) days. Both species increased the sucrose concentration by 18%, with a decrease of 52% in starch content. The RD4 time presented the highest mean starch concentration (0.19 mmol g−1 of the residue for H. courbaril and 0.27 mmol g−1 of residue for H. stigonocarpa). Increased proline concentrations were recorded for controls until RD2 for both species. For glycine betaine, the highest increases in treatments E26 and RD2 were observed for the H. courbaril species. Our rehydration period was not sufficient for total recovery of pre-stress concentrations of all studied solutes.
Keywords: Amazonia; Osmotic adjustment; Proline; Sucrose; Water stress